Laboratory mouse housing conditions can be improved using common environmental enrichment without compromising data - André, Viola; Gau, Christine; Scheideler, Angelika; Aguilar-Pimentel, Juan A.; Amarie, Oana V.; Becker, Lore; Garrett, Lillian; Hans, Wolfgang; Hölter-Koch, Sabine; Janik, Dirk; Moreth, Kristin; Neff, Frauke; et al. (PLoS biology, 2018)
Animal welfare requires the adequate housing of animals to ensure health and well-being. The application of environmental enrichment is a way to improve the well-being of laboratory animals. However, it is important to know whether these enrichment items can be incorporated in experimental mouse husbandry without creating a divide between past and future experimental results. Previous small-scale studies have been inconsistent throughout the literature, and it is not yet completely understood whether and how enrichment might endanger comparability of results of scientific experiments. Here, we measured the effect on means and variability of 164 physiological parameters in 3 conditions: with nesting material with or without a shelter, comparing these 2 conditions to a “barren” regime without any enrichments. We studied a total of 360 mice from each of 2 mouse strains (C57BL/6NTac and DBA/2NCrl) and both sexes for each of the 3 conditions. Our study indicates that enrichment affects the mean values of some of the 164 parameters with no consistent effects on variability. However, the influence of enrichment appears negligible compared to the effects of other influencing factors. Therefore, nesting material and shelters may be used to improve animal welfare without impairment of experimental outcome or loss of comparability to previous data collected under barren housing conditions.
Gesehen am 25.05.2020